Advanced Noise Mitigation Strategies in Image Processing: A Comprehensive Analysis and Optimization Study - Mongia, Vikas (International Journal of Computer Sciences and Engineering, 2022)
The advent of technology has shifted the representation of information from text to images. However, the image capturing process introduces noise, resulting in distortion and the generation of potentially misleading information. To address this challenge, it is essential to integrate noise handling mechanisms into existing image processing methods. Among these mechanisms, filtering stands out as a crucial strategy for mitigating noise effects. This research delves into the analysis of various noise handling mechanisms in the current context, aiming to identify optimized strategies for enhancing parameters in future implementations.